Diklat Sebagai Organisasi Belajar Dalam Teknologi Kinerja - Fifit Fitriansyah (Cakrawala - Jurnal Humaniora, 2018)
Rapid organizational development is possible thanks to the support of various other fields such as in the field of transportation technology, communication, computerization, and others. In this case, if the training is said to be an organization then it is necessary. Where the training itself is an institution engaged in education and training in order to improve the quality of Human Resources in accordance with the required performance indicators within an organization. For that, the existence of training in an organization is expected to form a good attitude as well as having the skills and skills in carrying out its duties in accordance with the position.